MITIGASI FRAUD DI SEKTOR PERBANKAN: PERAN MANAJEMEN RISIKO DAN AUDIT INTERNAL DENGAN MODERASI KOMITE AUDIT PADA BANK UMUM DAN SYARIAH - Indarti Indarti; Fahmi Oemar; Burhan Burhan (Komunitas Manajemen Kompetitif, 2026)
Fraud in the workplace is a form of financial crime that can have a significant impact on organizations globally. According to a recent report from the Association of Certified Fraud Examiners (ACFE), companies are estimated to lose approximately 5% of their total annual revenue due to fraudulent practices, with an average loss per case reaching approximately USD 1.7 million. In addition to economic losses, fraud can also damage a company's reputation, erode stakeholder trust, and threaten the continuity of its operations. Therefore, fraud mitigation (FM) efforts are a crucial element in implementing good corporate governance.Fraud mitigation plays a key role in preventing, detecting, and responding to potential fraud within an organization. Various studies have shown that the success of fraud mitigation is influenced by the effectiveness of risk management (MR) and internal audit activities (AAI). Adequate risk management implementation helps detect potential fraud risks early, while internal audit provides independent oversight and evaluation of the effectiveness of a company's internal control system.This study aimed to evaluate the influence of risk management and internal audit activities on fraud mitigation, and to examine the role of the audit committee in strengthening this relationship.The results showed that Risk Management and Internal Audit significantly influence fraud mitigation. The Audit Committee was not found to moderate the effect of Risk Management on fraud mitigation, but it was able to strengthen the influence of Internal Audit on fraud mitigation. These findings indicate that the effectiveness of Risk Management in mitigating fraud operates independently, while the effectiveness of Internal Audit in supporting fraud mitigation is optimized when supported by an effective Audit Committee.